From the accidental to articulated smart city: The creation and work of 'Smart Dublin'. (October 2019) - Coletta, Claudio; Heaphy, Liam; Kitchin, Rob
While there is a relatively extensive literature concerning the nature of smart cities in general, the roles of corporate actors in their production and the development and deployment of specific smart city technologies, to date there have been relatively few studies that have examined the situated practices by which the smart city unfolds in specific places. In this paper, we draw on three sets of interviews ( n = 114) and ethnographic fieldwork to chart the smart city ecosystem in Dublin, Ireland. We examine how the four city authorities have actively collaborated to frame a disparate and uncoordinated set of information and communication technology-led initiatives, what Dourish terms the 'accidental smart city', into an articulated vision of Dublin as a smart city. In particular, we focus on the work of 'Smart Dublin', a shared unit established to coordinate, manage and promote Dublin's smart city initiatives and to drive new economic development opportunities centred on corporate interventions into urban management and living. Our analysis highlights the value of undertaking a holistic mapping of a smart city in formation, and the role of political and administrative geographies and specialist smart city units in shaping that formation.